Elevated systemic immune-inflammatory index predicts poor coronary collateralization in type 2 diabetic patients with chronic total occlusion - Mao, Lin Shuang; Wang, Yi Xuan; Wu, Zhi Ming; Ding, Feng Hua; Lu, Lin; Shen, Wei Feng; Dai, Yang; Shen, Ying (Frontiers in Cardiovascular Medicine, 2024)
ObjectiveThis study compared the value of different systemic immune-inflammatory markers for evaluating coronary collateralization (CC) in patients with type 2 diabetes mellitus (T2DM) and chronic total occlusion (CTO).MethodsSystemic immune-inflammation index (SII), systemic inﬂammation response index (SIRI) and pan-immune-inﬂammation value (PIV) were calculated at admission in 1409 T2DM patients with CTO. The degree of coronary collaterals was estimated using the Rentrop scoring system and categorized into poor (Rentrop score 0 or 1) or good (Rentrop score 2 or 3) CC. The predictors of poor CC were determined by multivariate regression analysis, and the diagnostic potential of these indexes was analyzed by Receiver Operating Characteristic (ROC) curves.ResultsSII, SIRI and PIV levels increased stepwise across Rentrop score 0–3, with significantly higher levels in patients with poor CC than in those with good CC (P < 0.001). After adjusting for confounders, SII, SIRI and PIV (per tertile) remained independent factors for poor CC. SII predicted poor CC better than SIRI and PIV (AUC: 0.758 vs. 0.680 and 0.698, all P < 0.001). There existed an interaction between blood concentration of HbA1c and SII (P < 0.001), with high SII levels being associated with a greater risk (OR: 5.058 vs. 2.444) and providing a better predictive ability for poor CC (AUC: 0.817 vs. 0.731) in patients with HbA1c < 6.5% compared to those with HbA1c ≥ 6.5%.ConclusionOur study shows that elevated SII provides a better prediction for poor CC in T2DM patients with CTO especially at good glycemic control.